2020
DOI: 10.1098/rspb.2020.0838
|View full text |Cite
|
Sign up to set email alerts
|

‘What I cannot create, I do not understand’: functionally validated synergism of metabolic and target site insecticide resistance

Abstract: The putative synergistic action of target-site mutations and enhanced detoxification in pyrethroid resistance in insects has been hypothesized as a major evolutionary mechanism responsible for dramatic consequences in malaria incidence and crop production. Combining genetic transformation and CRISPR/Cas9 genome modification, we generated transgenic Drosophila lines expressing pyrethroid metabolizing P450 enzymes in a genetic background along with engineered mutations in the voltage-gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…We confirm the antagonistic effect of abamectin on all three Rdls, suggesting that abamectin also acts on Rdls at high doses in T. urticae . We therefore propose that the I321T GluCl3 mutation plays a role in abamectin resistance, but only in combination with synergistic additional factors that deserve more investigation 75 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirm the antagonistic effect of abamectin on all three Rdls, suggesting that abamectin also acts on Rdls at high doses in T. urticae . We therefore propose that the I321T GluCl3 mutation plays a role in abamectin resistance, but only in combination with synergistic additional factors that deserve more investigation 75 …”
Section: Resultsmentioning
confidence: 99%
“…We therefore propose that the I321T GluCl3 mutation plays a role in abamectin resistance, but only in combination with synergistic additional factors that deserve more investigation. 75…”
Section: Resultsmentioning
confidence: 99%
“…Homozygous kdr mutations at both nucleotides 1016 and 1534 of the voltage-gated sodium channel gene were characterized in the p-s population and might contribute to high resistance to permethrin. In fact, co-occurrence of multiple resistance mechanisms, such as the V1016G kdr mutation and overexpression of CYP9J28 , was shown to be synergistic in conferring pyrethroid resistance in genetically engineered Drosophila [ 62 ]. We noticed the p-s population had a longer survival time in the adult stage, moreover, the dissemination rate of DENV-1 in the p-s population was significantly higher than its parental population, Key West.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, research involving investigation of the synergistic interactions of enzyme overexpression and/or target-site mutations within a Drosophila-engineered unbiased framework has indicated that the synergistic action of different molecular mechanisms has a multiplicative effect in phenotype manifestation, at least for pyrethroids [44]. This implies that such an experimental system can be readily engineered, for example by stably integrating a TuCPR-expressing transgene together with an attP landing site for ΦC31 integrase or equivalent, which would minimize the "noise" induced by position effects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, functional expression of candidate CYP genes is routinely used for the investigation of their catalytic properties and substrate specificities. Moreover, the integration of the molecular genetics toolbox developed in model systems like Drosophila into insecticide resistance research (reviewed in [39][40][41]) has facilitated novel approaches that have significantly contributed to the validation of several candidate mutations conferring target-site resistance [42], P450 genes potentially conferring metabolic resistance [43], or their synergistic interactions [44], in the absence of confounding genetic effects.…”
Section: Introductionmentioning
confidence: 99%